2013
DOI: 10.1186/1471-2369-14-220
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep disturbances in renal transplant recipients

Abstract: BackgroundPoor sleep quality (SQ) and daytime sleepiness (DS) are common in renal transplant (RTx) recipients; however, related data are rare. This study describes the prevalence and frequency of self-reported sleep disturbances in RTx recipients.MethodsThis cross-sectional study included 249 RTx recipients transplanted at three Swiss transplant centers. All had reported poor SQ and / or DS in a previous study. With the Survey of Sleep (SOS) self-report questionnaire, we screened for sleep and health habits, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 53 publications
(68 reference statements)
0
29
0
19
Order By: Relevance
“…This study originally investigated 926 RTx recipients (Burkhalter et al, 2014), of whom 21.3% reported daytime sleepiness (ESS > 10) and 58.6% reported poor sleep quality (PSQI > 5); 249 RTx recipients participated in a sleep survey and 164 RTx participated in the subsequent sleep assessment to determine a preliminary sleep disorders diagnosis (Burkhalter et al, 2013); 49 had a putative diagnosis of SWD, of whom 30 participated in the bright light intervention study (Burkhalter et al, 2015). Within this latter group a high majority had low or no melatonin rhythm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study originally investigated 926 RTx recipients (Burkhalter et al, 2014), of whom 21.3% reported daytime sleepiness (ESS > 10) and 58.6% reported poor sleep quality (PSQI > 5); 249 RTx recipients participated in a sleep survey and 164 RTx participated in the subsequent sleep assessment to determine a preliminary sleep disorders diagnosis (Burkhalter et al, 2013); 49 had a putative diagnosis of SWD, of whom 30 participated in the bright light intervention study (Burkhalter et al, 2015). Within this latter group a high majority had low or no melatonin rhythm.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were recruited at the University Hospitals of Basel, Berne and Zurich and had all participated in a screening study to evaluate sleep disorders in these patients (Burkhalter et al, 2013;Burkhalter et al, 2014). The inclusion criteria were adult RTx recipients more than 1 year post-transplant and diagnosed with SWD (sleep assessment interview in the preceding study); German speaking; on stable immunosuppressive drugs and no signs of acute rejection.…”
Section: Participants Eligibility Criteria and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…14, 15 Earlier we reported that chronic insomnia was independently associated with the presence of depression in kTx recipients. 16 In the general population there is a strong and bidirectional relationship between depression and sleep.…”
Section: Introductionmentioning
confidence: 91%